Pertimbangan Hukum Hakim dalam Memutuskan Pihak Ketiga Sebagai Pelawan yang Baik dan Benar - Nadya Indah Ayuningthyas; Ahdiana Yuni Lestari (Universitas Muhammadiyah Yogyakarta, 2023)
It is not impossible that the Chairperson of the Court will issue a stipulation of execution confiscation Number 7/Pen.Pdt.Eks/2020/PN.Tsm which will create new problems for parties that have nothing to do with the case, namely third parties. This study aims to analyze the judge's considerations in deciding on a third party as a good and correct adversary in Decision Number 21/Pdt.Bth/2022/PN Tsm. This research is a normative juridical research using secondary data. Research materials were analyzed prescriptively. The results showed that the judge decided that the third party was a good and correct opponent by considering the evidence presented by the opponent. The evidence consists of documentary evidence in the form of an authentic acte and the presence of two witnesses. The authentic acte submitted by Pelawan is the Sale and Purchase Acte made before the PPAT, in which the authentic acte has a perfect and binding evidentiary value. The two witnesses presented by Pelawan have fulfilled the formal and material requirements. This is in accordance with the provisions of Article 164 HIR in conjunction with Article 169 HIR.